Implementation of a functional supportive programme for survivors of cerebro-vascular accidents and their caregivers at home - Kuugongelwa, Suama; Small, Louis (International Journal of Advanced Nursing Studies, 2017)
A cerebro-vascular accident is a devastating experience and those who survive the initial incident often suffer from a variety of physical disabilities. These disabilities frequently result in an adult becoming incapable of, or being limited in, the provision of ongoing effective self-care. In anticipation of improving such situations the researcher developed a supportive-educative programme to be conducted in a home-based setting. This programme formed part of the main study and was implemented over four days. The researcher considered these educative sessions to be an ideal approach for implementing the programme, because adjusting, stabilising and coping can only be facilitated and put into practice through interactive participation. Eight survivors of cerebro-vascular accidents and their caregivers, all of whom had participated in the main study, were selected for the training sessions. During these sessions, the purpose, objectives and content of the programme were presented and discussed. Following the sessions, the participants were encouraged to apply what they had learnt from the training. After two months the researcher and the participants came together to conduct an evaluation of the programme.